To explore agent technology in e-commerce mighty house agent / Phiyadharshini Thirumalai - Phiyadharshini, Thirumalai (2001)
Agent technology is becoming more popular among system designers who want their system to be more personalized, continuously running and semi-autonomous. These properties make agents useful for a wide variety of information and process management tasks. It should come as no surprise that these same qualities are particularly useful for the information-rich and process-rich environment of electronic commerce. As such agent technology in electronic commerce (e-commerce) would be essential to improve on-line shopping which is becoming more and more popular these days. It is in these roles that agent system designers have the challenge to accurately identify and the opportunity to prescribe innovative ways of doing business. This project would be to build an electronic house agent which uses agent technology. This agent mediated house agent would be able to search a few search engines simultaneously for information of the house which best meet the clients requirement. The information collected would be displayed on-line to the client. This house agent would be able to change and improve the perspective of e-house buying in Malaysia. Buyers would be able to get the precise information on what they want. The buyer would not need to browse the net on his own. The agents help would be seeked to get the correct information wanted according to their requirement specification. The agent would also be able to give its recommendation on which of the information displayed best suits the buyer.